Pengaruh Content Marketing Dan Influencer Marketing Terhadap Keputusan Pembelian Produk Kosmetik Lokal di Tiktok Shop (Studi Pada Mahasiswa Manajemen Universitas Buana Perjuanagan Karawang) - Shukmalla, Delia; Wike Pertiwi, Citra Savitri, (Jurnal Mirai Management, 2023)
This research is motivated by the transition of the offline market to a digital market where social media becomes a place to do digital marketing. This research focuses on the influence of content marketing and influencer marketing on purchasing decisions for local cosmetic products at TikTok Shop, with the research subjects being students of the 2019 Batch Management Study Program at Universitas Buana Perjuangan Karawang. The research method used is quantitative with an explanatory survey. The data was collected through a questionnaire after that using the multiple linear analysis method using IBM SPSS software. The results of this study indicate that partially content marketing and influencer marketing affect purchasing decisions and simultaneously content marketing and influencer marketing variables affect purchasing decisions Keywords: Content Marketing_1, Influencer Marketing_2, Purchase Decisiom_3.